Guest Editors: Healthy Prophetic Lifestyle - Norita Md. Norwawi; Fauziah Hassan; Norshuhani Zamin (Universiti Sains Islam Malaysia, 2024)
We are pleased to present this issue to readers as a special issue on Healthy Prophetic Lifestyle presented at the Prophetic Science International Conference (Al-FURSAN18) which was held on the 4th November to 5th November 2018 at Universiti Sains Islam Malaysia. The conference was jointly organized by NRGS Research Group on Prophetic Food and Islamic Science Institute. Rasulullah SAW is a perfect and exemplary model not only in spiritual, but also physical and mental well being through healthy nutritional diet. Thus this conference aims to gather scholars from various disciplines such as science and technology, Islamic studies and social sciences to discuss and share research findings on topics related to prophetic science on healthy and sustainable living. The discussion starts with the article by Mohd Rahman, Ummi Affah and Hana Maizuliana who presented on scientific evidences of complementary and prophetic medicine in managing dengue infection.